Pengharapan Mesias pada Masa Intertestamental - Ayub Sugiharto (Angelion, 2020)
AbstractThe arrival of a Messiah is an important hope in the life of the nation of Israel. Until now the Jews still had the expectations of the Messiah, without ever mentioning the name of the figure of the Messiah, both explicitly and implicitly. The existence of this hope can not be separated from the condition of Israel at that time, which has experienced all forms of oppression and social inequality in the era of Media-Persia, Greece, and Rome. The journey of this nation which is full of great struggles related to other nations through various wars, even captivity is very sad. In conditions of distress, persecution, captivity, they need the helping hand of others who are expected to be able to release and liberate them, they expect someone who is able to release all their suffering, but that hope does not come. This condition was made worse by the absence of a prophet among them, who became a direct link between Yahweh and them. The presence of a deliverer or personal savior who had been promised was certainly very much awaited by this nation. What was their hope for the presence of the Messiah during the Intertestamental, when God was silent and did not reveal His Word to His chosen people? This brief article, specifically, will discuss the evidence of the hope of the Messiah, where the source of hope came from, and what the expected Messiah was like.AbstrakKedatangan seorang Mesias merupakan pengharapan penting dalam kehidupan bangsa Israel.  Sampai saat ini orang Yahudi masih mempunyai pengharapan Mesias, tanpa pernah menyinggung nama dari sosok Mesias tersebut, baik secara eksplisit maupun implisit.  Adanya pengharapan tersebut sebenarnya tidak terlepas dari kondisi Israel saat itu, yang telah mengalami segala bentuk penindasan dan ketimpangan social di jaman Media-Persia, Yunani, maupun Romawi.  Perjalanan bangsa ini yang penuh dengan berbagai pergumulan hebat berkaitan dengan bangsa-bangsa lain melalui berbagai peperangan, bahkan penawanan yang sangat menyedihkan. Dalam kondisi tertekan, teraniaya, tertawan, mereka membutuhkan uluran tangan pihak lain yang diharapkan bisa melepaskan dan memerdekakan mereka, mereka mengharapkan adanya seseorang yang mampu melepaskan segala penderitaan mereka, namun harapan itu tidak kunjung datang.  Kondisi ini semakin bertambah parah dengan tidak adanya lagi seorang nabi di antara mereka, yang menjadi penghubung langsung antara Yahweh dengan mereka. Hadirnya seorang pembebas atau pribadi penyelamat yang pernah dijanjikan tentu sangat dinanti-nantikan oleh bangsa ini.  Seperti apakah pengharapan mereka akan kehadiran Mesias pada masa Intertestamental, ketika Allah berdiam diri dan tidak menyatakan Firman-Nya kepada umat pilihan-Nya?  Tulisan singkat  ini, secara spesifik akan membahas tentang bukti pengharapan Mesias, dari mana  sumber pengharapan itu berasal, dan seperti apa Mesias yang diharapkan itu.